William D. Bynum papers - Bynum, William D. (William Dallas), 1846-1927.
Correspondence primarily relating to the National Democratic Party convention held in Indianapolis, Ind., prior to the U.S. presidential election of 1896, and to the party's support of the gold standard. Correspondents include Calvin Tomkins, Charles Tracey, Joseph E. Washington, and Thomas A. Wilson.
U.S. representative from Indiana.
Collection material in English.
Keywords: Tomkins, Calvin, -- 1858-1921 -- Correspondence; Tracey, Charles, -- 1847-1905 -- Correspondence; Washington, Joseph E. -- 1851-1915 -- Correspondence; Wilson, Thomas A., -- active 1896 -- Correspondence; National Democratic Party (U.S. : 1896-1900); Gold standard; Political conventions -- Indiana -- Indianapolis; Presidents -- United States -- Election -- 1896.; Third parties (United States politics); Indiana -- Politics and government; Indianapolis (Ind.) -- History; United States -- Politics and government -- 1865-1900.; Representatives, U.S. Congress. -- Indiana